2021
DOI: 10.1093/biosci/biab027
|View full text |Cite
|
Sign up to set email alerts
|

The Promise and Pitfalls of Environmental DNA and RNA Approaches for the Monitoring of Human and Animal Pathogens from Aquatic Sources

Abstract: Novel forensics-inspired molecular approaches have revolutionized species detection in the wild and are particularly useful for tracing endangered or invasive species. These new environmental DNA or RNA (eDNA or eRNA)–based techniques are now being applied to human and animal pathogen surveillance, particularly in aquatic environments. They allow better disease monitoring (presence or absence and geographical spread) and understanding of pathogen occurrence and transmission, benefitting species conservation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 110 publications
0
25
0
Order By: Relevance
“…Environmental DNA‐based conservation approaches are redefining our ability to monitor and protect vulnerable species, and our study demonstrates the varied applications possible when such approaches are applied to the study and conservation of migratory species with complex life cycles, such as endangered sea turtles (Adams et al, 2019; Beng & Corlett, 2020; Farrell, Whitmore, et al, 2021; Farrell, Yetsko, et al, 2021; Lacoursiere‐Roussel et al, 2016, 2018). This study has demonstrated the utility of species‐specific C .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Environmental DNA‐based conservation approaches are redefining our ability to monitor and protect vulnerable species, and our study demonstrates the varied applications possible when such approaches are applied to the study and conservation of migratory species with complex life cycles, such as endangered sea turtles (Adams et al, 2019; Beng & Corlett, 2020; Farrell, Whitmore, et al, 2021; Farrell, Yetsko, et al, 2021; Lacoursiere‐Roussel et al, 2016, 2018). This study has demonstrated the utility of species‐specific C .…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, we revealed the ability to collect data for population genetics studies through shotgun sequencing or conventional PCR of eDNA extracted from sand crawl samples. These approaches open a variety of conservation and health applications for sea turtle eDNA, from surveying population range shifts, to simultaneous host and pathogen monitoring, to conducting noninvasive population genetics on nesting females and hatchlings (Farrell, Whitmore, et al, 2021; Farrell, Yetsko, et al, 2021; Yetsko et al, 2021). We previously successfully employed the C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline ddPCR tetraplex assay presented here can be repurposed and adjusted to advanced technologies, including new pathogens of interest or analytical methods, which will foster scientific research output and expand the molecular surveillance toolbox. For example, applying occupancy and co-occurrence modeling approaches on the detection signals of different pathogens enables detection probabilities even if all samples return negative ( Willoughby et al, 2016 ; Laurin et al, 2020 ) and provides a cost-efficient tool for aquaculture surveillance ( Farrell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%